Clinical Problem Solving: An Older Woman With Weakness from Head to Toe. (January 2022) - Hartmann, David A.; Bock, Meredith; Douglas, Vanja; Gerdts, Josiah; Ramani, Biswarathan; Shah, Maulik
A 67-year-old woman was admitted to our hospital for progressive weakness, dysphagia, muscle pain, and weight loss. Here we detail the clinical problem solving involved in diagnosing and treating her immune-mediated necrotizing myopathy caused by anti-HMGCoA reductase autoantibodies. Interestingly, this diagnosis coincided with discovery of a gastrointestinal stromal tumor (GIST) and positivity for anti-nuclear matrix protein (anti-NXP2), another myositis specific autoantibody.